(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
This article is devoted to the process of digitization of agriculture in the Republic of Uzbekistan and its efficiency indicators. The data are taken from the analysis of statistical reports issued by the Statistics Committee of the Republic of Uzbekistan and cover the indicators of agriculture in the Republic of Uzbekistan since 2010. We used foreign experience to solve the problem. The analysis revealed that the efficiency of the agricultural digitization process is positively correlated.